Chromatographic analysis of phytochemicals in the peel of Musa paradisiaca to synthesize silver nanoparticles (2020)
This research work usedMusa paradisiaca(banana) peels as a natural solvent,assorted with the precursorAgNO3(10 mM) to perform the green synthesis of silvernanoparticles. The phytochemical components present in theMusa paradisiacapeelextracts were determined by gas chromatography coupled to a mass spectrometer(GC-MS), and it was possible to identify the compounds: 1.2 Ethanediol (60.0261%) and 2.3 Butanediol (11.2 %); these -diols represent a highly reducing agent formetals, since they act as a solvent for the metal precursor behaving as a reducingagent, and facilitating the formation of nanoparticles. Likewise, the synthesized silvernanoparticles were subjected to a washing and drying treatment to be subsequentlycharacterized by means of UV-Vis and XRD techniques, resulting in a wavelength of411 nm, which is characteristic of these metallic nanoparticles, and achieving theidentification of the face-centered cubic structure (fcc) of the metallic silver, with anaverage particle size of 21.8 nm according to the Debye-Scherrer equation.